Time course of blood pressure changes immediately after maximal exercise - Nakahara, H.; Miyamoto, T.; Nakanishi, Y.; Kinoshita, H. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The aim of this study was to investigate the effect of exhaustive exercise on the time course of arterial blood pressure (BP) and heart rate (HR) during upright resting (inactive) and loadless pedaling (active) recovery from a bicycle exercise to exhaustion. Methods: The subjects were 11 healthy normotensive males. Systolic, diastolic and mean BP, and HR were recorded every 20 s for the initial 6 min of the recovery period. Results: The time course of all BP measures during inactive and active recovery was characterized by a marked and sudden drop during the initial 20-s period, followed by a quick rise. This was followed by a gradual decline till the end of the recovery period. The time course of HR recovery, on the other hand, exhibited a smooth decline without the initial drop. With active recovery, the initial drop of diastolic and mean BP was less than the inactive recovery. After the 20 s period, the diastolic BP and HR were kept slightly higher with the active recovery than the inactive recovery. Conclusions: A sudden drop of the BP occurred at the initial recovery period of postcycle exercise to exhaustion though HR did not show such a change. The initial BP drop could be attenuated by the actively pedaling the cycle without load.